″Methodology of formulation of the controlled from distance course is discipline «Design»″ - Dontsova, M. V. (Problems of Engineer-Pedagogical Education, 2018)
In the article the considered possibility and expediency of introduction of the controlled from distance studies are with interactive presentation of material on replacement of old methods of conduct of educational process in INSTITUTION of higher learning. On the example of course «Design» is described general view of course, basic modules (resources and elements) that is used for organization of educational trajectory in the process of study of educational discipline, and also application of interactive technologies is reasonable in on - line environment, that extends possibilities of both teacher and student in organization of their studies. The further scientific searches of author are related to determination of problems in the field of креативного development of students during a computer design and work of ways of realization of model of forming of conceptual development of innovative computer methodology and her practical realization that must promote effectiveness of educational design product development, in the conditions of Kharkiv Trade and Economics Institute of Kyiv National University of Trade and Economics. It will allow to look after the dynamics of this process and more detailed to consider the article of research.